BCL-2, HER1, HER2, HER3 and HER4 expression in primary colorectal adenocarcinoma - Ahmad Zubir, Nurul Mahirah (2017)
In Malaysia, CRC is the most frequently reported cancer among males and second in females with the prevalence of 16.4% and 10.7%, respectively. Most cases occur sporadically, only 5% of the cases are inherited. There is a 50% risk of recurrence for the CRC survivor. Hence biomarkers to improve the prognosis, treatment outcomes and risk assessment are in dire need. The potential biomarkers include BCL-2 and HERs family members (HER1, HER2, HER3, and HER4). BCL-2 is an anti-apoptotic protein and its expression has been associated with tumour grading, staging, and prognosis. It affects tumour genesis by inhibiting cell apoptosis. Presence of BCL-2 expression enhances cancer survival rate. HERs family members are known as a surface receptor. Its activation occurs via ligands binding, leading to downstream signalling that influences cell proliferation. Mutations in HERs family members lead to activation of a series of signalling cascade which has numerous effects on protein expression. HER1, HER2, HER3 and HER4 aberrations in signalling contributes to malignancies, gene amplification and enhanced transcription in the CRC. This study aims to determine the protein expression of BCL-2 and HERs family members in CRC cases, using immunohistochemistry (IHC) technique. A total of 94 FFPE samples were collected from the Hospital Serdang archives from year 2008 until year 2015. Data on demographic and clinicopathologic were retrieved from the database. Protein expressions were detected in the cytoplasm, membranous, or/and nucleus region. The expressions were scored with semi-quantitative scoring system and graded as 0 (absent), 1+ (weak), 2+ (moderate), or 3+ (strong). Association test was used to determine the p - value (p < 0.05). BCL-2 expression was seen immunopositive in 26.6% cases. HERs family members showed immunopositivity in 31.9%, 13.8%, 42.6%, and 31.9% in HER1, HER2, HER3, and HER4 respectively. There was a significant association between HER1 and HER3 expression (p < 0.001), HER1 and HER4 expression (p = 0.019) and between HER3 and HER4 expression (p = 0.019). Significant association was seen between BCL-2 and HER1 expression (p = 0.022). HER1/HER3 co-expression was significantly associated with tumour grading (p = 0.030) and HER3/HER4 co-expression was significantly related with lymph node metastasis (p = 0.018). HER1 expression was associated with age (p = 0.018), Malay ethnicity (p = 0.038), tumour grading (p = 0.011), and diabetes mellitus (p = 0.044). A significant association was seen between HER2 and diabetes mellitus (p = 0.024). HER3 expression was significantly associated with gender (p = 0.027), tumour grading (p = 0.023), lymph nodes metastasis (p = 0.049), and smoking (p= 0.033). Likewise, HER4 expression was significantly associated with ethnicity (p < 0.001) and tumour grading (p = 0.021). This study shows that BCL2 and the HERs family members are overexpressed in CRC. The implications of these results for the CRC biomarkers are that, generally, overexpression of HERs family members are more likely inclined towards poor prognosis. While BCL-2 failed to show any relationship with demographic and clinicopathologic parameters. Results in coexpression among antibodies indicated relation and dependency with each other through downstream of pathways. BCL-2, HER1, HER2, HER3 and HER4 could be further developed for targeted therapy receptors and prognostic biomarkers for CRC.